Protocol for the effectiveness of multimonth refill of antituberculosis drugs (MORAD) on treatment success among people with drug-susceptible tuberculosis in rural eastern Uganda: a non-inferiority randomised trial - Jonathan Izudi; Francis Bajunirwe; Adithya Cattamanchi (BMJ Public Health, 2024)
Introduction: Multimonth dispensing of antituberculosis (TB) drugs reduces frequent visits and costs associated with longer travel distances to a TB clinic. We will evaluate the effectiveness of multimonth dispensing of anti-TB drugs on treatment success in individuals with drug susceptible TB in rural eastern Uganda, and explore its relevance and appropriateness from the stakeholders’ perspectives. Methods and analysis: In this open-label, non-inferiority, individually randomised trial, we will randomise 260 participants to either the intervention (multimonth dispensing of anti-TB drugs) or control arm (routine care) and follow-up for 6 months. Intervention participants will receive monthly anti-TB refills for 2 months then a 2-month refill for 4 months, totalling four visits. Control participants will receive routine care comprising biweekly anti-TB refills for 2 months and monthly refills for 6 months, totalling eight visits. The primary outcome will be treatment success (treatment completion or cure) at month 6. Secondary outcomes will include adherence to anti-TB treatment over 6 months measured by self-report and pill counts, and sputum smear conversion at months 2 and 6 defined as a change in sputum smear status from positive to negative among bacteriologically confirmed individuals. Data will be analysed using a generalised linear mixed model at a 5% significance level, reported as a risk difference with a 95% CI. A formative qualitative study will be conducted among stakeholders at the national, district and health facility levels and people with TB including their treatment supporters to inform the intervention’s relevance, appropriateness and implementation. Qualitative data gathered through focus group discussions and indepth and key informant interviews will be transcribed and analysed using content analysis. Ethics and dissemination: The Infectious Diseases Institute Research Ethics Committee and the Uganda National Council for Science and Technology approved the protocol. Findings will be disseminated to all stakeholders through presentations, synthesised reports and manuscript publication.
Keywords: Tuberculosis; Uganda; Multimonth dispensing